2018
DOI: 10.1111/sode.12320
|View full text |Cite
|
Sign up to set email alerts
|

Participant roles in preschool bullying: The impact of emotion regulation, social preference, and quality of the teacher–child relationship

Abstract: The present work investigated whether emotion regulation and social preference were associated with participant roles in bullying as a function of the quality of the relationship with teachers. Participants were 332 children (172 boys), in the age of 42–76 months (M = 58.74; SD = 7.84). Peer nominations were employed to assess social preference and participant roles (bullying, victimization, defending the victim, and outsider behavior). Teachers completed the Emotion Regulation Checklist, which yields the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
2
29
0
1
Order By: Relevance
“…By contrast, there was some consistency in reports by children and their teachers on 5-year-olds’ aggression, victimisation and defending [ 8 ]. Additionally, based on peer and teacher reports, Camodeca et al [ 43 ], in research in Italy with 2–6-year-olds, collapsed reinforcing and assisting into a “follower” role. They found high intercorrelations between most of the roles, suggesting that these were not well distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, there was some consistency in reports by children and their teachers on 5-year-olds’ aggression, victimisation and defending [ 8 ]. Additionally, based on peer and teacher reports, Camodeca et al [ 43 ], in research in Italy with 2–6-year-olds, collapsed reinforcing and assisting into a “follower” role. They found high intercorrelations between most of the roles, suggesting that these were not well distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also found that the quality of the student-teacher relationship may play a crucial role in reducing the risk of victimization by bullies (Camodeca and Coppola 2019;Iotti et al 2020;Author et al 2018a, b). According to the attachment perspective on studentteacher relationships (Pianta 1999), teachers represent a "secure base" that may provide positive relational models, characterized by closeness and support.…”
Section: Introductionmentioning
confidence: 96%
“…Okul öncesi öğretmenleri ile çocukların duygu düzenleme becerileri hakkında yapılan çalışmalara bakıldığında ilişkisel tarama modeli çalışmalarına daha çok rastlanılmaktadır. Bu çalışmaların bulgularında öğretmen-öğrenci etkileşiminin çocuğun duygu düzenleme becerisi ile birlikte akademik başarısına (Garner ve Waajid, 2008), duygusal davranışlarına (Zinsser, Bailey, Curby, Denham ve Bassett, 2013), akran zorbalığına (Camodeca ve Coppola, 2019), problemli davranışlarına (Sutherland vd., 2018) etkisi olduğu görülmektedir.…”
Section: Introductionunclassified